2010
DOI: 10.1016/j.jvs.2010.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Arm vein conduit vs prosthetic graft in infrainguinal revascularization for critical leg ischemia

Abstract: Arm vein conduits, even when spliced, are superior to prosthetic grafts in terms of midterm assisted primary patency, secondary patency, and leg salvage in infrapopliteal bypasses for CLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 38 publications
1
39
0
1
Order By: Relevance
“…Whereas the addition of a venous interposition cuff to a prosthetic graft may provide a minor benefit, 28-30 we were limited in drawing significant statistical conclusions from the use of these and the aforementioned bypass conduit choices. Many investigators, however, have shown promising results with such alternative conduit choices 31-33 and further studies focusing on their effectiveness are in progress within our region. Second, the patient cohort studied was predominantly Caucasian.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the addition of a venous interposition cuff to a prosthetic graft may provide a minor benefit, 28-30 we were limited in drawing significant statistical conclusions from the use of these and the aforementioned bypass conduit choices. Many investigators, however, have shown promising results with such alternative conduit choices 31-33 and further studies focusing on their effectiveness are in progress within our region. Second, the patient cohort studied was predominantly Caucasian.…”
Section: Discussionmentioning
confidence: 99%
“…Existing data evaluating prosthetic conduits (PCs) vs alternative vein (AV) sources (arm vein, small saphenous vein, composite/spliced vein segments) in the absence of usable SSGSV are limited and report mixed results. 4,5 The purpose of this study was to evaluate the optimal conduit for below-knee popliteal artery bypass in the absence of usable SSGSV.…”
mentioning
confidence: 99%
“…For distal targets, such as IPA, we recommend the use of AAC, which is supported by this study as well as others. 20,[24][25][26] In the future, randomized, prospective studies are needed to compare the efficacy of NAC over AAC and, possibly, GSV. We are currently in the process of performing similar analyses on the larger Vascular Quality Initiative database, which may also allow for better evaluation of subgroups.…”
Section: Discussionmentioning
confidence: 99%